(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Urinary tract infections (UTIs) are among the most frequent bacterial infections worldwide. Their prevalence in young males is often underestimated. This study aimed to determine the frequency, causative organisms, and antimicrobial resistance patterns of UTIs in young male patients at DHQ Abbottabad. Material & Methods: A descriptive cross-sectional study was conducted over six months at District Headquarters Hospital Abbottabad. Two hundred young male patients aged 15–40 years presenting with urinary symptoms were recruited through consecutive sampling. Patients with structural abnormalities, catheterization, immunocompromised states, or recent antibiotic use were excluded. Midstream urine samples were analyzed for microscopy and culture. Organisms were identified and tested for antibiotic susceptibility using Clinical Laboratory Standards Institute (CLSI) guidelines. Data were analyzed with SPSS v25, applying Chi-square test for associations (p<0.05). Ethical approval was obtained from the Institutional Review Board of DHQ Hospital Abbottabad. Results: Out of 200 patients, 46 (23%) had culture-proven UTI. The mean age was 28.4 ± 6.2 years. Dysuria (65%) and urinary frequency (52%) were the most common symptoms. Escherichia coli was the predominant pathogen (72%), followed by Klebsiella pneumoniae (15%) and Proteus mirabilis (9%). Nitrofurantoin (78%) and ciprofloxacin (65%) were most effective, while resistance was highest against co-trimoxazole (70%). Recurrent infections were significantly associated with culture positivity (p=0.032). Conclusion: UTIs are relatively frequent among young males in Abbottabad. Clinical vigilance, routine urine cultures, and rational antibiotic prescribing are essential. Hygiene education and antimicrobial stewardship are recommended.